2015
DOI: 10.17511/ijpr.2015.i04.12
|View full text |Cite
|
Sign up to set email alerts
|

A study on glycemic control and related complications in type I diabetic children

Abstract: Introduction: Type I Diabetes Mellitus is a common, chronic, metabolic syndrome characterized by hyperglycaemia as a cardinal biochemical feature. Patients with diabetes mellitus face an increased risk of morbidity and mortality due to micro and macrovascular complications caused by diabetes. There is lack of Indian studies on diabetic children. Hence this study was undertaken to know glycaemic control and related complications in type I diabetes mellitus. Materials and methods: This is a Prospective study con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Patil and Gaikwad carried out a kinetic study on the Co(II)-promoted oxidation of acetamide using bromamine-T (BAT) in an aqueous medium (Scheme 79). 107 The reaction exhibits first-order kinetics in terms of both [BAT] and [acetamide], and an increase in their concentrations led to an increase in the specific rate. It was observed that the addition of allyl acetate, sodium chloride and p-toluenesulfonamide, as well as a change in the pH, did not have any impact on the reaction rate.…”
Section: Scheme 78 Oxidation Of Metformin Hydrochloride By Bromamine-tmentioning
confidence: 99%
“…Patil and Gaikwad carried out a kinetic study on the Co(II)-promoted oxidation of acetamide using bromamine-T (BAT) in an aqueous medium (Scheme 79). 107 The reaction exhibits first-order kinetics in terms of both [BAT] and [acetamide], and an increase in their concentrations led to an increase in the specific rate. It was observed that the addition of allyl acetate, sodium chloride and p-toluenesulfonamide, as well as a change in the pH, did not have any impact on the reaction rate.…”
Section: Scheme 78 Oxidation Of Metformin Hydrochloride By Bromamine-tmentioning
confidence: 99%
“…They are reliable, robust and the most efficient internal combustion engines . However, diesel engines are suffer form their high emission drawbacks like particulate matters (PM), total gaseous hydrocarbons (THC), nitrogen oxides (NO x ), sulfur oxides (SO x ) and smoke ,. It is seemed that the most suitable way to reduce of these emissions is the using of alternative fuels made from renewable sources instead of the commercial fuels .…”
Section: Introductionmentioning
confidence: 99%